E-Learning and Its Impact on Students and Their Learning Styles - PRAKASH, MR. JAY (The journal of contemporary issues in business and government, 2021)
Electronic learning (e-Learning) is the most advance and modern method of teaching and learning process. In this process teachers and students both are involved virtually and synchronize accordingly in order to deliver the knowledge full content. These days due to COVID-19, life was stuck somewhere in every family, every school / college but then e-learning was the only medium to teach students with safety at home. In this paper, a brief discussion is done on concept of e-learning and a survey has been done in nearby society where students from middle class and lower class families lives. In future as use of technology is keep increasing, more and more education methods will be required to uplift the lower class families by supporting them and dealing with them in knowledge full way.